Optical characterisation of oxidised carbon nanohorn nanofluids for direct solar energy absorption applications. (October 2019) - Gimeno-Furio, A.; Hernandez, L.; Barison, S.; Agresti, F.; Cabaleiro, D.; Mancin, S.
Highlights: Oxidised carbon nanohorns were synthesized without the addition of surfactants. Oxidised and non carbon nanohorns stability was studied at high temperature. A deep optical study, including scattering, was carried out for both nanofluids. Both of them were stable after three months even at high temperature. The absorption is highly improved for both nanofluids compared to the base fluid. Abstract: Carbon nanohorns and oxidised carbon nanohorns-based nanofluids were characterised by taking one step forward. The advantage of studying oxidised carbon nanohorns is that they are surfactant-free. The stability of both nanofluids was checked after a 3-month preparation period at high temperature, which comes closer to real applications. Two different dynamic light scattering (DLS) systems were used to measure stability at high temperature before being compared. A deep optical analysis was run. An integrating sphere was attached to the classic spectrophotometer to determine the scattering of nanofluids. After obtaining the experimental values of the optical parameters for both nanofluids, the Kubelka-Munk Theory was applied to obtain optical coefficients. Finally, the scattering albedo was calculated to facilitate comparisons with the literature. Studying both nanofluid types provided us with new knowledge about their potential use as direct solar absorbers in solar thermal collectors.